Reduced Effect of Anticonvulsants on AMPA Receptor Palmitoylation-Deficient Mice - Iizumi, Madoka; Oota-Ishigaki, Akiko; Yamashita, Mariko; Hayashi, Takashi (Frontiers in Pharmacology, 2021)
AMPA receptors are responsible for fast excitatory synaptic transmission in the mammalian brain. Post-translational protein S-palmitoylation of AMPA receptor subunits GluA1-4 reversibly regulates synaptic AMPA receptor expression, resulting in long-lasting changes in excitatory synaptic strengths. Our previous studies have shown that GluA1 C-terminal palmitoylation-deficient (GluA1C811S) mice exhibited hyperexcitability in the cerebrum and elevated seizure susceptibility without affecting brain structure or basal synaptic transmission. Moreover, some inhibitory GABAergic synapses-targeting anticonvulsants, such as valproic acid, phenobarbital, and diazepam, had less effect on these AMPA receptor palmitoylation-deficient mutant mice. This work explores pharmacological effect of voltage-gated ion channel-targeted anticonvulsants, phenytoin and trimethadione, on GluA1C811S mice. Similar to GABAergic synapses-targeting anticonvulsants, anticonvulsive effects were also reduced for both sodium channel- and calcium channel-blocking anticonvulsants, which suppress excess excitation. These data strongly suggest that the GluA1C811S mice generally underlie the excessive excitability in response to seizure-inducing stimulation. AMPA receptor palmitoylation site could be a novel target to develop unprecedented type of anticonvulsants and GluA1C811S mice are suitable as a model animal for broadly evaluating pharmacological effectiveness of antiepileptic drugs.